The Indo-Pacific Strategy under the Biden Administration’s Southeast Asia Policy: Developments, Limitations, and China’s Countermeasures - Li, Jinyuan (Pacific International Journal, 2025)
The United States has advanced the "Indo-Pacific Strategy," a geo-strategic framework aimed at integrating the Indo-Pacific region for strategic positioning to counterbalance China’s influence. Consequently, the U.S. Southeast Asian policy has undergone significant transformations and adjustments, shaped by the "Indo-Pacific Strategy," which revolves around the pivotal linkage between the Indian Ocean and the Pacific. Southeast Asia, located at the heart of both oceans, plays a crucial role in determining the success or failure of this strategy. It is not only a vital component of the U.S. "Indo-Pacific Strategy" but also a significant strategic partner of China and a key region for China’s neighboring diplomacy. Across multiple U.S. administrations, the "Indo-Pacific Strategy" has emerged as a primary policy instrument in the U.S. strategic competition with China. It also represents a pivotal variable influencing the strategic decisions of Southeast Asian countries in the China-U.S. rivalry. As Southeast Asia has become a strategic fulcrum in the U.S. "Indo-Pacific Strategy" aimed at containing China, it is imperative to promptly study and precisely understand the impact and trajectory of the U.S. strategy on China-Southeast Asian relations. Formulating targeted, forward-thinking, and directive countermeasures is of utmost importance. These countermeasures are crucial for breaking the encirclement posed by the U.S. "Indo-Pacific Strategy" against China, reinforcing the China-ASEAN comprehensive strategic partnership, and fostering a conducive neighboring environment.